Chemical Compound Of Liquid Smoke Derived From Leaf Of Piper betle L And Piper crocatum Ruiz & Pav - Dodi Irwandi; Ai Emalia Sukmawati; Dian Maria Ulfah (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2018)
Liquid smoke made from green betel leaf (Piper betle L) and red betel leaf (Piper crocatum Ruiz & Pav) has been made by pyrolysis. To determine the allegations of the chemical compounds contained in these two liquid smoke, they were tested by Gas Chromatography–Mass Spectrometry (GC-MS) method. Based on the test results it was found that there were 7 suspected compounds in the liquid smoke of green betel leaf and 30 compounds in red betel liquid smoke. The main compounds contained in the liquid smoke of green betel leaf are Isamoxole as the anti-allergic, 5,10-Diethoxy-2,3,7,8-tetrahydro-1H, 6H-dipyrrolo [1,2-a; 1', 2'-d ] Pyrazine as an antifungal and 3,5-Dimethoxyphenol has the potential to be antibacterial while in red betel leaves are 4- (1H-1,3-Benzodiazol-2-yl) phenol and Benzene, 1,2,3-trimethoxy-5- (2 -propenyl) - Bioactivity potential of the two compounds has not been found.